Papel da ranitidina como meio de aprimorar a qualidade do exame de colangiopancreatografia por ressonância magnética - Torres, Lucas Rios [UNIFESP] (2013)
OBJECTIVE: To assess the impact of oral ranitidine on the imaging quality in magnetic resonance cholangiopancreatography (MRCP). MATERIALS AND METHODS: Thirty-two patients underwent MRCP with 3D and 2D acquisitions, and three strategies for suppression of the gastrointestinal fluid signal: a) only at fasting; b) 12 hours after ingestion of 300 mg ranitidine; c) after oral administration of gadolinium solution. Three observers reviewed the images with a focus on the degree of visualization of the biliopancreatic tree. The interobserver agreement was evaluated with the kappa test. The difference between techniques and acquisition modalities were evaluated by means of average grading scores. RESULTS: The three strategies for suppression of the gastrointestinal fluid signal presented high reproducibility. The results with suppression of the gastrointestinal fluid signal with ranitidine where similar to those obtained with fasting, and both were worse than those obtained with gadolinium solution. The 3D acquisitions surpassed 2D only in terms of visibility of the cystic duct and gallbladder, and were inferior or equivalent in the other biliopancreatic ductal segments. CONCLUSION: The use of ranitidine does not seem justified in the evaluation of the biliopancreatic tree at MRCP, since 2D MRCP with fasting allows the visualization of ductal structures with high quality and reproducibility in the majority of cases.